Education on Disease Risk Factors in Adapting New Habits to Prospective Hajj Pilgrims at KBHI Bisri-Pusri Palembang City - Emma Novita Emma; Agita Diora Fitri; Tia Sabrina; Andyra Priandhana; Muhammad Musa; M.Taufik Wijaya (International Journal Of Community Service, 2021)
Health istitha'ah is the health ability of the pilgrims physically and mentally with a measurable health assesment. It is essential for every citizen who will perform the hajj pilgrimage. The Indonesian Ministry of Health through the Non-Infectious Disease Integrated Service Post (Posbindu PTM) implements an early detection and prevention program for non-infectious diseases in sub-districts, schools or colleges, institutions or workplaces, and Hajj guidance groups (KBIH) especially for pilgrims. The department of public health and community medicine (IKM-IKK) of the Faculty of Medicine, Sriwijaya University perform an education on the detection of risk factors for non-infectious diseases and physical fitness assesment of prospective pilgrims in the context of community service activities at KBIH Bisri Palembang. Examinations were done on 40 prospective pilgrims using the Rockport test method. The results of the examination showed that the 24 pilgrims had moderate fitness level (60%). The blood pressure test results showed that 9 pilgrims had hypertension (22%) and the nutritional status test showed that 20 pilgrims were overweight and obese (38.5%). In addition, there is an assesment for prospective hajj pilgrims in order to understanding risk factors for non-infectious diseases. The result shows that there is a significant increase in understanding about non-infectious diseases in the adaptation of new habits.